Green at home. Green on the road? An examination of whether individuals who practice eco-sustainable behaviours in their daily lives maintain these habits while travelling / James Brian Aday and Kelly Virginia Phelan - Aday, James Brian; Phelan, Kelly Virginia (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA (UiTM), Malaysia, 2013)
Recent data indicates eco-sustainable tourism accounts for an increasing percentage of total worldwide tourism receipts. The economic influence, leveraged with the positive environmental implications associated with sustainability practices, has resulted in the emergence of eco-sustainability as an up and coming area of study. This study aims to examine whether tourists who employ eco-sustainable practices in their daily routines maintain these practices while traveling. This research will essentially bridge the gap between conflicting research which indicates a willingness to pay more, and studies which exhibit price sensitivity in relation to travelers' green tendencies. Furthermore, this study will help to ascertain whether tourists seek out environmentally-friendly properties, or whether these entities are viewed as simply a convenience while travelling. This research is unique in its approach, since it examines which traits consumers are looking for in a green hospitality business and whether these firms benefit financially from increased demand if environmentally conscious policies are adopted.